Laser treatment of medical skin disease in women - C. LaRosa, MD; A. Chiaravalloti, MD; S. Jinna, MD; W. Berger, BS; J. Finch, MD (Wolters Kluwer, 2017)
Laser treatment is a relatively new and increasingly popular modality for the treatment of many dermatologic conditions. A number of conditions that predominantly occur in women and that have a paucity of effective treatments include rosacea, connective tissue disease, melasma, nevus of Ota, lichen sclerosus (LS), notalgia paresthetica and macular amyloidosis, and syringomas. Laser therapy is an important option for the treatment of patients with these conditions. This article will review the body of literature that exists for the laser treatment of women with these medical conditions.